Efek Neuroprotektif Fraksi Air Daun Semanggi (Marsilea crenata Presl.) secara In Vitro - Burhan Ma'arif; Muslim, Menara; Riyanti, Anisa Eka; Guhir, Abdul Malik; Amalia, Dilla; Saidah, Nisfatul Lailatus; Anggraini, Wirda; Atmaja, Ria Ramadhani Dwi; Laswati, Hening; Agil, Mangestuti (Universitas PGRI Adi Buana, Surabaya, 2021)
Background: Estrogen deficiency can trigger several diseases, one of which is neurodegenerative. Neurodegenerative begins with neuroinflammation, which triggers the activation of microglia cells resulting in a pro-inflammatory activity. Potential and relatively safe therapy to use to overcome it is by using phytoestrogen compounds. Marsilea crenata Presl. is a plant that contains phytoestrogens. Objective: The purpose of this study was to analyze the neuroprotective effect of the water fraction of Marsilea crenata Presl. leaves which was shown by inhibition of neuroinflammation and marked by increased levels of MHC II against HMC3 microglia cells. Methods: IFN-γ is induced into HMC3 microglia cells for 24 hours to cause inflammatory conditions. Marsilea crenata Presl. leaves water fraction was given at a dose of 62,5; 125; and 250 µg / ml. Analysis of the neuroprotective effect of HMC3 microglia cells using the ICC method with the aid of the CLSM instrument. Results: The results of this study indicate that the water fraction of Marsilea crenata Presl. leaves can reduce MHC II expression at concentrations of 125 and 250 μg / ml with values ​​of 465,748 and 460,884 AU at p less than 0,005. Conclusion: This study concludes that the water fraction of Marsilea crenata Presl. has neuroprotective activity shown at doses of 125 and 250 μg/ml which can reduce MHC II expression in HMC3 microglia cells induced by IFN-γ. The ED50 value which has a neuroprotective effect is at a dose of 0,582 μg/ml.